2015
DOI: 10.3892/ol.2015.3201
|View full text |Cite
|
Sign up to set email alerts
|

Association between the ornithine decarboxylase G316A polymorphism and breast cancer survival

Abstract: Abstract. Ornithine decarboxylase (ODC) is a significant rate-limiting enzyme in polyamine synthesis, required for normal cell growth, and is highly expressed in various malignancies, including colorectal and breast cancer. In the present study, the associations between the ODC G316A single nucleotide polymorphism (SNP) and breast cancer-specific survival were investigated. In addition, the functional effects of this SNP were examined in the MCF-7 human breast cancer cell line. The present study recruited 300 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
7
1
Order By: Relevance
“…The induction of ODC1 might contribute to increased cellular proliferation rates, which in turn predisposes to, and possibly potentiates, HCC. Moreover, ODC1 is overexpressed in several human cancers such as colon, liver [84], and breast carcinomas [85]. A similar role can be hypothesized for ARAF; indeed, an overexpression of RAF kinases (i.e., ARAF, BRAF, and CRAF) is associated with activation of the ERK pathway, which in turn increases cell proliferation in vitro and in vivo [86].…”
Section: Cancermentioning
confidence: 77%
“…The induction of ODC1 might contribute to increased cellular proliferation rates, which in turn predisposes to, and possibly potentiates, HCC. Moreover, ODC1 is overexpressed in several human cancers such as colon, liver [84], and breast carcinomas [85]. A similar role can be hypothesized for ARAF; indeed, an overexpression of RAF kinases (i.e., ARAF, BRAF, and CRAF) is associated with activation of the ERK pathway, which in turn increases cell proliferation in vitro and in vivo [86].…”
Section: Cancermentioning
confidence: 77%
“…increased ornithine levels can reduce ammonia and its associated oxidative stress via the urea cycle 19,20 , which may contribute to a protective mechanism as lower oxidative stress levels are associated with lower breast cancer risk 21 . However, ornithine is a substrate for producing polyamine via enzyme ornithine decarboxylase, which promotes the progression of cancer 5,11,22,23 . Although the biological mechanisms of action through which ornithine contributes to carcinogenesis are conflicting, the former mechanism may be dominant based on the findings from the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies on breast and colorectal cancers reported that the G316A GG genotype is associated with a more favorable outcome than the AG/AA genotypes [ 18 , 19 ]. We investigated the association between SNP genotype and survival in a publicly available colorectal cancer cohort of 290 cases (Sieber, R2 Genomics Analysis and Visualization platform; , accessed on 3 August 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Three possible genotypes result from the SNP: GG, AG and the variant AA which occurs at a low frequency of 7–10% in the general population [ 14 , 18 ]. A previous study has shown that the transcriptional repressor Mad1 suppresses the activity of the ODC1 promoter in colon cancer cells containing the A-allele but not the G-allele, and other studies have also reported that the E-box repressors MAD4 (MXD4) and MXI1 bind less strongly in cells homozygous for the GG genotype [ 18 , 19 ]. These findings suggest allele-specific regulation of ODC1 by E-box transcription factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation